Pengaruh Pembelajaran Kewirausahaan, Lingkungan Pergaulan, dan Latar Belakang Ekonomi Keluarga Terhadap Minat Berwirausaha Mahasiswa STIE-GK Muara Bulian - Muryati Muryati; Ade Jermawinsyah Zebua (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2020)
This study aims to determine: 1) The ef ect of learning entrepreneurship on entrepreneurial interest. 2)The influence of the social environment on the interests of entrepreneurship. 3) The ef ect of familyeconomic background on entrepreneurial interest. 4) The ef ect of entrepreneurial learning, socialenvironment, and family economic background on entrepreneurial interest. This research is acomparative causal study with a quantitative approach. The variables in this study are learningentrepreneurship, social environment, and family economic background as independent variables, whilethe variables of entrepreneurial interest as the dependent variable. The population in this study were allstudents who studied Entrepreneurship Subjects at Graha Karya Muara Bulian School of Economicswho had been active in entrepreneurship courses. The technique used to determine the sample was arandom sampling technique, amounting to 35 respondents. The results of this study indicate that 1)entrepreneurial learning has a positive and significant ef ect on entrepreneurial interest 2) socialenvironment has a positive and significant influence on entrepreneurial interest 3) family economicbackground has a negative ef ect on entrepreneurial interest 4) entrepreneurial learning, socialenvironment, and family economic background together positive and significant ef ect on studentinterest in entrepreneurship.